Handbook of flexible organic electronics : materials, manufacturing and applications - Logothetidis, Stergios (Woodhead Publishing series in electronic and optical materials, 2014)
Organic flexible electronics represent a highly promising technology that will provide increased functionality and the potential to meet future challenges of scalability, flexibility, low power consumption, light weight, and reduced cost. They will find new applications because they can be used with curved surfaces and incorporated in to a number of products that could not support traditional electronics. The book covers device physics, processing and manufacturing technologies, circuits and packaging, metrology and diagnostic tools, architectures, and systems engineering. Part one covers the production, properties and characterisation of flexible organic materials and part two looks at applications for flexible organic devices.